2011
DOI: 10.1039/c0dt00720j
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear, tetranuclear and polymeric complexes in copper(ii) perchlorate/pyridine-2,6-diamidoxime chemistry: synthetic, structural and magnetic studies

Abstract: The initial use of pyridine-2,6-diamidoxime (pdamoH(2)) in metal cluster and polymer chemistry is described. Depending on the reaction conditions employed, the Cu(ClO(4))(2)·6H(2)O/pdamoH(2) system has provided access to the dinuclear compound [Cu(2)(pdamoH)(2)(ClO(4))(2)(MeOH)(2)] (1), the chain-like polymer [Cu(2)(pdamoH)(2)](n)(ClO(4))(2n) (2) and to the tetranuclear cluster [Cu(4)(pdamo)(2)(pdamoH)(2)](ClO(4))(2) (3). Single-crystal, X-ray crystallography reveals different coordination modes for the pdamoH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Although the bridging properties of oximic ligands have been extensively studied, e.g., nearly exhaustively in the case of group VIII metals (Fe, , Ru, Os, Co, , Ni, ,, and Pd) and partially for some representatives of group I (Cu ,, ), II (Zn ,, Cd), III (Gd), IV (Ti and Zr), VI (Cr), and VII (Mn ,, ), there are no reports on oximato-bridged platinum complexes. Moreover, to the best of our knowledge the novel di-/trimer(s) exhibit a unique six-membered diplatinacycle as well as represent the first example of oxime/oximato ligands coordinated to the platinum atom via oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Although the bridging properties of oximic ligands have been extensively studied, e.g., nearly exhaustively in the case of group VIII metals (Fe, , Ru, Os, Co, , Ni, ,, and Pd) and partially for some representatives of group I (Cu ,, ), II (Zn ,, Cd), III (Gd), IV (Ti and Zr), VI (Cr), and VII (Mn ,, ), there are no reports on oximato-bridged platinum complexes. Moreover, to the best of our knowledge the novel di-/trimer(s) exhibit a unique six-membered diplatinacycle as well as represent the first example of oxime/oximato ligands coordinated to the platinum atom via oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…So far, polymetallic Zn complexes have been obtained using ligands such as salicylaldo(keto)oximes, 27 pyridyl oximes, 28 and aliphatic dioximes. 29 Chemical structures of the oximes and their derivatives used for the preparation of multi-Zn complexes are presented in Scheme 1 with corresponding literature citations highlighted in blue. Thus, a 36-membered macrocyclic hexaoxime ester derivative with Zn 3 La core/shell tetranuclear cluster structure was obtained by condensation of dialdehyde with diamine using La 3+ (core metal) and Zn 2+ (shell metal) as a novel core/shell template.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Due to cited potential applications of these polymetallic systems, there is a need for controlled synthesis methods for preparation of these compounds, as well as a need for different polydentate ligands that are able to act as bridges in such systems. So far, polymetallic Zn complexes have been obtained using ligands such as salicylaldo­(keto)­oximes, pyridyl oximes, and aliphatic dioximes . Chemical structures of the oximes and their derivatives used for the preparation of multi-Zn complexes are presented in Scheme with corresponding literature citations highlighted in blue.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of dinuclear Cu­(II) complexes doubly bridged by two N,O oximato ligands has been reported showing strong antiferromagnetic coupling, usually displaying J values, in an absolute value, higher than −500 cm –1 (even diamagnetism at room temperature in some cases), so the strong antiferromagnetic coupling for complexes 1 – 3 was not unexpected. Previous works, in this field, have shown that the mechanism of the interaction between the two Cu­(II) ions and the double oximato-bridge depends on the good orbital overlap in Cu–(RNO) 2 –Cu core (R = different groups), as the most relevant factor. , The unpaired electron of each Cu­(II) ion is located on the d x 2 – y 2 magnetic orbital, so the planarity of the bridging region favors stronger antiferromagnetic coupling.…”
Section: Resultsmentioning
confidence: 99%